Identifying directions for improving the regulation of the circulation of high-technology innovations in the European Union - Davydiuk, Oleksandr; Bakalinska, Olga; Malovatskyi, Oleksii; Tarasov, Oleh; Senyk, Yurii (Eastern-European Journal of Enterprise Technologies, 2026)
This study examines a system of procedures and techniques for regulating relations that create, transfer, and implement high-tech innovations in the European Union, through the prism of the promising EUROPEAN INNOVATION ACT (EIA). The current means of identifying high-tech innovations in the European Union have been studied, as well as the prospects for their improvement when implementing the EIA. This work has found that the process of regulatory influence on innovation circulation in the EU is not uniform. It has been proven that the current model of regulatory influence in the EU is not focused on the proper identification of high-tech innovations. It also does not provide simplification or stimulation of their use but only has a general focus on the intensification of all innovations in the EU economy. It was determined that within the EU there is a need to improve the methods for regulating the circulation of high-tech innovations. A study of directions to reform the innovation ecosystem through the implementation of the EUROPEAN INNOVATION ACT has been conducted. The feasibility of forming a definition of high-tech innovation was substantiated. The necessity of registering the criteria for distinguishing high-tech innovation from its other varieties has been proven. The need for the formation of a holistic system of regulatory influence based on the life cycle (Innovation Life Cycle) of high-tech innovation was identified. This study is aimed at compiling proposals for improving the regulatory processes of innovation circulation in the EU. The results could be used in improving the official rules of innovation circulation in the EU, as well as at the level of national systems of EU member states. They could also be applied to make strategic public management decisions, form state policy on the circulation of innovations; the findings might lay the groundwork for further scientific research on these issues